Relationship between chlorophyll contents and spectral properties of frond 9 and 17 of mature oil palm - A. Tarmizi, W.; Muharam, Farrah Melissa; Amiruddin, A. D. (Institute of Plantation Studies, Universiti Putra Malaysia, 2017)
Presently non-invasive light-based chlorophyll determination has become the standard for a quick overview of general plant health and yield estimation. For oil palm which is a perennial crop, however, the determination should be done by considering effects of oil palm age and frond number. In this study, spectral reflectance obtained from (a) spectroradiometer and (b) SPAD were used to investigate variations in chlorophyll a, b, and total. It was found that SPAD values were inadequate to predict leaf chlorophyll content in young and mature oil palm for both frond 9 and 17 (r2 = 0.0001 – 0.40 and r2 = 0.019 – 0.16, respectively). Correlation analysis showed that spectroradiometer reflectance at 700 - 1350nm wavelength has relationship with chlorophyll content as high as r = 0.4. There was also other peaks at 400nm, 1600nm, and 1900nm which could be of interest in future studies.